REDO BLOOD DONATE APP - B.SURESH RAM, G.KARTHIK REDDY, P.MAHESH BABU, SHAIK IRFAN,B.ANIL (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
"REDO Blood Connect" is an Android-based app. In the event of an emergency, this application can help users find needed blood. Here Users may seek information about contributors and beneficiaries with ease using their mobile phones. Users must first register with the app in order to view all of the information about the blood group it has to offer. The user may look for information about blood donors by searching for it according to the respective districts or nearby areas. The user may make a call or send a message straight from this software to the mobile phones of the donors. With the rapid expansion of COVID-19throughout the world the number of requests for the blood and the blood platelets has continued to rise, and also the rise in the number of postings soliciting blood donors on social sites like WhatsApp, Facebook, Twitter and Instagram. Finding a right blood donor for the patient is a challenging task in almost every country especially during this pandemic. There are plethora of blood donor locator applications but holds a series of drawbacks with which the receiver could not able to get the blood on time and the right blood. We designed the application which is user friendly and could able to reach the broad area of the people in need in very less time and can save many lives. Our application has a very special features which differentiate between the donors who are available to give the blood and the donors who have other reasons not to give the blood like suffering from covid-19, given blood recently, out of station, diagnosed with some disease and health issues. In our App the donor can choose enable or disable to give the blood according to his willingness or due to the mentioned reasons. As a result, the person who needs the blood can connect to the right and readily available donors without wasting the time. This app is best to find right people who are willing to give blood at the right time